The promise of financial services regulatory theory to address disinformation in content recommender systems - Owen Bennett (Internet Policy Review, 2021)
This article argues that the European regulatory approach to disinformation online is stymied by inappropriate regulatory theories. On that basis, this article seeks to advance an alternative theoretical approach, inspired by the contemporary European paradigm of financial services regulation. It outlines how the key theories underpinning financial services regulation could engender policy solutions that are both more rights-protective and more responsive to the role played by content recommender systems in compounding the policy problem of disinformation online. It assesses the extent to which these alternative regulatory theories manifest in the draft EU Digital Services Act.
Keywords: 300; Disinformation; Regulatory theory; Content recommender systems; DigitalServices Act